2012
DOI: 10.1159/000335423
|View full text |Cite
|
Sign up to set email alerts
|

MIP-3α Expression in Macrophages Is NOD Dependent

Abstract: Background: The first identified susceptibility gene for Crohn’s disease, NOD2, acts as a sensor for the bacterial-wall peptidoglycan fragment muramyl dipeptide (MDP) and activates the transcription factor nuclear factor-ĸB (NF-ĸB). Upon NF-ĸB activation, intestinal macrophages (IMACs) induce expression of macrophage inflammatory protein (MIP)-3α to attract memory T lymphocytes. We therefore investigated the influence of NOD2 ligation of IMAC differentiation and functional MIP-3α induction. Methods: Human embr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 100 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…CCL20 was highly inducible in PBMCs, in particular through TLR2/1, NOD2 and IL-1β. NOD2 induced release of CCL20 is supported by Hausmann et al, who showed that CCL20 release from macrophages is NOD dependent [ 29 ]. We showed for the first time that PBMCs from the UC group tend to have a stronger NOD2, TLR2/1 and IL-1β induced CCL20 release than PBMCs from the CD group, suggesting a disease dependent difference in CCL20 involvement.…”
Section: Discussionmentioning
confidence: 93%
“…CCL20 was highly inducible in PBMCs, in particular through TLR2/1, NOD2 and IL-1β. NOD2 induced release of CCL20 is supported by Hausmann et al, who showed that CCL20 release from macrophages is NOD dependent [ 29 ]. We showed for the first time that PBMCs from the UC group tend to have a stronger NOD2, TLR2/1 and IL-1β induced CCL20 release than PBMCs from the CD group, suggesting a disease dependent difference in CCL20 involvement.…”
Section: Discussionmentioning
confidence: 93%